Global Attractor for a Chemotaxis Model with Reaction Term - Xueyong Chen; Jianwei Shen (Journal of Applied Mathematics)
A chemotaxis model with reproduction term in a bounded domain Ω⊂Rn is discussed in this paper, where n=2,3. First, the existence of a global-in-time solution is given, and then a global attractor for this model is obtained.